Assessment made incredibly easy ! (Springhouse Corporation, 1997)
Reviews important details of taking patient histories and doing physical assessments. Includes photographs, numerous halftone illustrations, and summaries of key points. 22 U.S. contributors. Softcover. DNLM: Nursing Assessment--handbooks.